Split-step timing of professional and junior tennis players - Filipcic, A.; Leskosek, B.; Filipcic, T. (Journal of Human Kinetics, 2017)
The purpose of the study was to determine the timing of a split-step in three categories of tennis players in four groups of strokes. Subjects were divided into three groups: male and female junior, and male professional tennis players. During two tournaments, all matches were recorded with two fixed video cameras. For every stroke, the timing of the split-step between the opponent`s impact point when hitting the ball and the player`s split-step was measured. A two-way analysis of variance (ANOVA) was used to determine the differences between groups of strokes, players and the interaction Player x Stroke Group. A Tukey post-hoc test was employed to determine specific differences. The results revealed differences between players in detecting the opponent`s movement, stroke and ball flight, which were reflected in different split-step timings. Each tennis player has his/her own timing mechanism which they adapt to various game situations. Response times differ significantly depending on the game situation. On average, they are the lowest in the serve, and then gradually rise from the return of the serve to baseline game, reaching the highest values in specific game situations. Players react faster in the first serve than in the second one and in the return of the serve, the response times are lower after the return of the second serve